2005
DOI: 10.1562/2004-08-05-ra-263
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in DNA Synthesis During Two-Photon Microscopy of Intrinsic NAD(P)H Fluorescence

Abstract: Two-photon laser scanning microscopy (TPLSM) of endogenous reduced nicotinamide adenine dinucleotide (NAD(P)H) provides important information regarding the cellular metabolic state. When imaging the punctate mitochondrial fluorescence originating from NAD(P)H in a rat basophilic leukemia (RBL) cell at low laser powers, no morphological changes are evident, and photobleaching is not observed when many images are taken. At higher powers, mitochondrial NAD(P)H fluorescence bleaches rapidly. To assess the limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is the case in LLLT, but also in certain cases during multiphoton microscopy [33], [50]. However larger amounts of perturbation can exceed the repair capacity of the cell, and toxic effects gradually take place: increase in intracellular calcium concentration [15], [23], [39], membrane depolarisation [51], ROS diffusion inside the cytoplasm [14], destruction of nuclear membranes [37], breakdown of DNA synthesis [20], [49] and finally apoptotic cell death [37].…”
Section: Review Of Photodamage Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is the case in LLLT, but also in certain cases during multiphoton microscopy [33], [50]. However larger amounts of perturbation can exceed the repair capacity of the cell, and toxic effects gradually take place: increase in intracellular calcium concentration [15], [23], [39], membrane depolarisation [51], ROS diffusion inside the cytoplasm [14], destruction of nuclear membranes [37], breakdown of DNA synthesis [20], [49] and finally apoptotic cell death [37].…”
Section: Review Of Photodamage Mechanismsmentioning
confidence: 98%
“…Different molecules may be primarily involved depending on the wavelength, but a following step generally involves the creation of ROS and the subsequent rise of oxidative stress [38]. This stress is then transducted differently depending on the amount of the perturbation [15], [49]: if perturbation is limited, repair and protection mechanisms take place that induce cell proliferation. This is the case in LLLT, but also in certain cases during multiphoton microscopy [33], [50].…”
Section: Review Of Photodamage Mechanismsmentioning
confidence: 99%
“…It has been shown that these signals in cells/tissues mainly have origins in mitochondria, 63 , 64 and the measurement of NADH, Fp and redox ratios, i.e., Fp/(Fp+NADH) or NADH/(Fp+NADH) provides an index of mitochondrial metabolic states. 15,16,27,28 The fluorescence spectra of NADH and oxidized flavoproteins (Fp) in suspensions of isolated mitochondria are shown in Fig.…”
Section: Basic Principles and Advantages Of Mitochondrial Redox Immentioning
confidence: 99%
“…We have previously employed two-photon excited fluorescence intensity-based metabolic imaging techniques in monolayer cultures (Indig et al, 2000; Nichols et al, 2005; Tiede and Nichols, 2006), multicell tumor spheroids (Nichols and Webb, 1998), and the organ of Corti of intact but excised murine cochlea (Tiede et al, 2007). Our goal has been to develop and evaluate techniques for non-invasively measuring cellular metabolism so we can better study, understand and ultimately foster the development of better treatments for a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%